Effect of asthma, COPD, and ACO on COVID-19: A systematic review and meta-analysis - Uruma, Yuka; Manabe, Toshie; Fujikura, Yuji; Iikura, Motoyasu; Hojo, Masayuki; Kudo, Koichiro (PloS one, 2022)
The prevalence of asthma, chronic obstructive pulmonary disease (COPD), and asthma-COPD overlap (ACO) in patients with COVID-19 varies, as well as their risks of mortality. The present study aimed to assess the prevalence of asthma, COPD, and ACO as comorbidities, and to determine their risks of mortality in patients with COVID-19 using a systematic review and meta-analysis. We systematically reviewed clinical studies that reported the comorbidities of asthma, COPD, and ACO in patients with COVID-19. We searched various databases including PubMed (from inception to 27 September 2021) for eligible studies written in English. A meta-analysis was performed using the random-effect model for measuring the prevalence of asthma, COPD, and ACO as comorbidities, and the mortality risk of asthma, COPD, and ACO in patients with COVID-19 was estimated. A stratified analysis was conducted according to country. One hundred one studies were eligible, and 1,229,434 patients with COVID-19 were identified. Among them, the estimated prevalence of asthma, COPD, and ACO using a meta-analysis was 10.04% (95% confidence interval [CI], 8.79-11.30), 8.18% (95% CI, 7.01-9.35), and 3.70% (95% CI, 2.40-5.00), respectively. The odds ratio for mortality of pre-existing asthma in COVID-19 patients was 0.89 (95% CI, 0.55-1.4; p = 0.630), while that in pre-existing COPD in COVID-19 patients was 3.79 (95% CI, 2.74-5.24; p<0.001). France showed the highest prevalence of asthma followed by the UK, while that of COPD was highest in the Netherlands followed by India. Pre-existing asthma and COPD are associated with the incidence of COVID-19. Having COPD significantly increases the risk of mortality in patients with COVID-19. These differences appear to be influenced by the difference of locations of disease pathophysiology and by the daily diagnosis and treatment policy of each country.